Strategic Management Process in the Making of Financial Statements in Ministry of Foreign Affairs - Prayogo, Bambang (FIA UB, 2018)
This Study aims to learn about the strategic management of Ministry of Foreign Affairs in the making of financial statement. It was carried out in Financial Bureau of Ministry od Forein Affairs in Jakarta. The result reveal that the strategic management process in the making of financial statement in the Ministry of Foreign Affairs are consist of strategy formulation, strategy implementation, and strategy evaluation. The important point to be noticed is the stakeholder analysis hadn’t been used properly and the TOWS matrix wasn’t used to formulate strategy development.